Association of P53 codon 72 polymorphism and lung cancer in an ethnic Iranian population - Eydian, Z; Asna'ashari, A M H; Behravan, J; Sharifi-Rad, J; Entezari Heravi, R (Cellular and Molecular Biology, 2016)
Lung cancer is one of the most common causes of cancer death worldwide. Molecular genetic studies indicated that activation of dominant oncogenes or inactivation of tumor suppressor genes and the presence of polymorphism in these genes correlated with prevalence of new lung cancers. P53 as a tumor suppressor gene located at 17p13 chromosome and it is one of the most well-known mutant genes in all cancer types. Mutation in P53 can disturb the transcriptional function and suppression of cell cycle control and increase in cell division and amplification. We can predict the susceptibility of people inside a society to lung cancer with evaluation of P53 gene polymorphism. A total of 200 patients with lung cancer and 200 healthy controls participated in this case-control study. Genomic DNA was extracted from blood samples and PCR-RFLP analyses were used to genotype the P53 gene polymorphism in codon 72 of exon 4, chromosome 17. Among 200 lung cancer patients and 200 controls, there was no significant correlation between sexuality and cigarette smoking status. We did not find any relationship between cigarette smoking status and genotypes or pack-years but there was a significant correlation between cigarette smoking status and adenocarcinoma patients (P=0.03). The results of the present study revealed that there is no association between P53 codon 72 polymorphism and increased risk of lung cancer in patients and controls but according to results of adenocarcinoma in never-smoker patients, it seems that environmental factors may have more important role than genetic susceptibility in our ethnic Iranian population.